2020
DOI: 10.1002/chem.201905499
|View full text |Cite
|
Sign up to set email alerts
|

One Guest or Two? A Crystallographic and Solution Study of Guest Binding in a Cubic Coordination Cage

Abstract: A crystallographic investigation of a series of host–guest complexes in which small‐molecule organic guests occupy the central cavity of an approximately cubic M8L12 coordination cage has revealed some unexpected behaviour. Whilst some guests form 1:1 H⋅G complexes as we have seen before, an extensive family of bicyclic guests—including some substituted coumarins and various saturated analogues—form 1:2 H⋅G2 complexes in the solid state, despite the fact that solution titrations are consistent with 1:1 complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 64 publications
2
53
0
Order By: Relevance
“…The combined volume of two ID guests (74%) significantly exceeded the value of 55 ± 9% of the host cavity volume (409 Å 3 ), which Rebek showed a while ago afforded optimal guest binding in solution [50,51]. However, a crystalline sponge experiment was performed under highly forcing and non-equilibrium conditions using a large excess of the guest; we [48] and others [52][53][54] have observed packing coefficients for guests inside supramolecular host cavities of >80% when favourable interactions such as π-stacking between multiple guests and favourable interactions between guests and the cage interior surface result in a particularly compact guest array. In dilute solution-the conditions under which guest binding is normally evaluated-we can imagine that for this reason, the second binding constant K 2 would be substantially smaller than the first binding constant K 1 , in which case, the single-guest binding would dominate the solution speciation behaviour [48].…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…The combined volume of two ID guests (74%) significantly exceeded the value of 55 ± 9% of the host cavity volume (409 Å 3 ), which Rebek showed a while ago afforded optimal guest binding in solution [50,51]. However, a crystalline sponge experiment was performed under highly forcing and non-equilibrium conditions using a large excess of the guest; we [48] and others [52][53][54] have observed packing coefficients for guests inside supramolecular host cavities of >80% when favourable interactions such as π-stacking between multiple guests and favourable interactions between guests and the cage interior surface result in a particularly compact guest array. In dilute solution-the conditions under which guest binding is normally evaluated-we can imagine that for this reason, the second binding constant K 2 would be substantially smaller than the first binding constant K 1 , in which case, the single-guest binding would dominate the solution speciation behaviour [48].…”
Section: Resultsmentioning
confidence: 83%
“…A crystal structure of the cage/guest H/ID complex could be obtained using the crystalline sponge method that we have used in previous work by preparing crystals of the free host cage H by a solvothermal synthesis, followed by slow cooling [28], and immersing them in a concentrated solution of ID in MeOH for several hours, which resulted in guest uptake without loss of crystallinity [48]. Details of the structure are shown in Figures 3-5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aqueous solution studies using 37 also suggested that the multiple guest binding may occur in the presence of high guest concentrations. 171 …”
Section: Repercussions and Applications Of The Aqueous Host–guest Chementioning
confidence: 99%
“…As a benchmark of this adaptation, the packing coefficient, the ratio of guest to host volume, is usually compared to Rebek's 55 % solution [21] . Only if strong intermolecular forces such as hydrogen bonds contribute to the complex’ stability, an excess of these 55±9 % is observed [22] …”
Section: Introductionmentioning
confidence: 99%